Design and Development of Human Excretory System Model to Teach A Biology Concept in Ilorin, Nigeria - Olumorin, Charles Olabode; Babalola, Ebenezer Omolafe; Ayoola, Desire Adunola (Universitas Pendidikan Indonesia (UPI), 2022)
Meaningful instruction takes place only with the appropriate use of instructional materials, especially in their real form. Inability to have access to mammalian internal organs is one of the challenges in teaching some concepts in Biology. Lack of practical experience in the teaching and learning of Biology that leads to poor mastery of important scientific skills and concepts could be among those factors responsible for students’ poor performance in Biology. Hence, the need to design and develop the Model of Human Excretory System (MHES) to teach Biology concepts in secondary schools. The study was a developmental research design, ADDIE instructional system design model was adopted in the production and evaluation of the model. The development involved four out of the five stages of the ADDIE model. The adapted phases include ADDE; these are Analysis, Design, Development, and Evaluation. Findings of this study revealed that: The model of the human excretory system was successfully developed using four (ADDE) out of the five stages of the ADDIE model as a guide and the cost of developing the model of the human excretory system was determined and found to be cheaper through the use of locally sourced materials.